2020
DOI: 10.1021/acs.chemrev.9b00687
|View full text |Cite
|
Sign up to set email alerts
|

Porous Aromatic Frameworks (PAFs)

Abstract: Porous aromatic frameworks (PAFs) represent an important category of porous solids. PAFs possess rigid frameworks and exceptionally high surface areas, and, uniquely, they are constructed from carbon−carbon−bond−linked aromatic-based building units. Various functionalities can either originate from the intrinsic chemistry of their building units or are achieved by postmodification of the aromatic motifs using established reactions. Specially, the strong carbon−carbon bonding renders PAFs stable under harsh che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
320
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 500 publications
(323 citation statements)
references
References 348 publications
1
320
0
2
Order By: Relevance
“…It has been demonstrated that di-, tri-, and tetraaryl adamantanes have a great tendency to form various types of supramolecular systems in the solid state (e.g., encapsulating crystals 8 and were used in syntheses of porous aromatic frameworks). 9 The adamantane skeleton was also used as a rigid linker between chromophoric groups. 10 Therefore, molecules bearing several pyrenyl groups in a well-defined spatial arrangement might be of interest for developing solid-state emitters, sensors, or self-assembled nanomaterials.…”
Section: Results and Discussionmentioning
confidence: 99%
“…It has been demonstrated that di-, tri-, and tetraaryl adamantanes have a great tendency to form various types of supramolecular systems in the solid state (e.g., encapsulating crystals 8 and were used in syntheses of porous aromatic frameworks). 9 The adamantane skeleton was also used as a rigid linker between chromophoric groups. 10 Therefore, molecules bearing several pyrenyl groups in a well-defined spatial arrangement might be of interest for developing solid-state emitters, sensors, or self-assembled nanomaterials.…”
Section: Results and Discussionmentioning
confidence: 99%
“…PAFs built by C‐C aromatic‐based building units hold great promise for gas storage and capture because of their ultrahigh surface area and high physicochemical stability. [ 98 ] Multinuclear 1 H, 13 C, and 29 Si SSNMR has been efficiently employed for structural characterization of various PAFs including PAF‐1, [ 99 ] PAF‐5, [ 100 ] JUC‐Z2, [ 101 ] JUC‐Z12, [ 102 ] mPAF‐1, [ 103 ] sulfonated PAFs [ 104 ] and PAFPORP. [ 105 ] PFA‐1 possesses high surface area of 7100 m 2 g −1 and exceptional thermal/hydrothermal stabilities.…”
Section: Ssnmr Characterization Of Other Microporous Materialsmentioning
confidence: 99%
“…Thus, COFs have been regarded as the ideal candidates for the cathode substrate of Li-S batteries. [47][48][49][50] The huge π-conjugated system of COFs could provide abundant routes for electron transfer [51] and the small molar mass makes it possible for COFs-based batteries to achieve high mass specific capacity. [52,53] Unfortunately, the performances of batteries with COFs as cathode matrices are barely satisfactory, probably due to the lack of active centers contributing to the fixation of polysulfides.…”
mentioning
confidence: 99%